Kombinasi Algoritma Sequential Search dan Fitur Autocomplete Pada Aplikasi Arsip (E-Arsip) Perpustakaan Berbasis Web - Muhammad Furqon Sjofjan; Fauziah Fauziah; Rima Tamara Aldisa (Journal of Information System Research (JOSH), 2023)
Files have the capability of being a source of data, therefore the existence of archives in an agency plays an important role in broad activities, given the importance of archives, consideration is needed in data management to ensure agency archives are stored properly and are easy to find. Searching for data through the site has been greatly developed along with the support of improved equipment, data search can be done using the search information stored in the program, search algorithms are a collection of software programs created to make it easier for clients to find and track data. Currently in search enter the word or phrase byuser to find data that is still difficult to find. Therefore we need features that can help users in searching. So this research was made and the application used two algorithms that can help in typing words or phrases namelyAutocomplete in order to assist clients in searching for data, and algorithms Sequential Search to make it easier to find client data. The average run time of the Sequential Search algorithm from 250 user data is 0.00496 seconds, and the word input search process with Autocomplete yields results for 100 percent of the 250 corresponding database data.